ANALISIS KESEJAHTERAAN RUMAH TANGGA PETANI PADI SAWAH DI NAGARI IV KOTO MUDIEK KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Hardi, Jendri; Gusriati; Herda Gusvita (Jurnal Research Ilmu Pertanian, 2021)
This study aims to analyze the level of household welfare of lowland rice farmers from the GSR approach and to analyze the factors that affect the level of household welfare of lowland rice farmers in Nagari IV Koto Mudiek, Batang Kapas District, Pesisir Selatan District. This research was conducted in August 2020, with a sample size of 59 people from 147 populations. Data consisted of primary data and secondary data with descriptive quantitative data analysis using GSR analysis and multiple linear regression. The results showed that the level of household welfare of lowland rice farmers in Nagari IV Koto Mudiek, Batang Kapas District, Pesisir Selatan Regency was categorized as less prosperous household with a GSR value of 2.607% (> 1). Together, there is a significant influence on food expenditure, non-food expenditure, income from farming, age of the farmer, number of family dependents, education level and rice field area on the level of welfare. Partially which has a significant effect   on   the   welfare   level   of   food   expenditure,   non-food expenditure, education   level   and   rice   field   area.   The   coefficient   of determination (R2) is 0.851 or 85.1%.